2010
DOI: 10.2147/plmi.s9988
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of hematological indices of infants, children, and adolescents in Port Harcourt, Nigeria

Abstract: Lack of standard local reference values have been a problem facing hematological practice in Nigeria. Our aim was to establish reference hematological values from infancy to adolescence for future use in Nigeria. Methods: A total of 1,021 apparently healthy Nigerian children aged 0-17 years were recruited for this cross-sectional descriptive study from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…6 The few small studies conducted in African population syndicate differences in normal values compared with those for populations in industrialized countries. 7 Lower values for haemoglobin, red blood cells, haematocrit, mean corpuscular volumes, platelets and neutrophils and higher monocytes and eosinophils levels were reported in African population compared to similar population in Western parts. 8 Many studies have revealed that reference values vary with several parameters such as ethnic origin, genetics, gender, altitude and environmental factors 9 .…”
Section: Introductionmentioning
confidence: 91%
“…6 The few small studies conducted in African population syndicate differences in normal values compared with those for populations in industrialized countries. 7 Lower values for haemoglobin, red blood cells, haematocrit, mean corpuscular volumes, platelets and neutrophils and higher monocytes and eosinophils levels were reported in African population compared to similar population in Western parts. 8 Many studies have revealed that reference values vary with several parameters such as ethnic origin, genetics, gender, altitude and environmental factors 9 .…”
Section: Introductionmentioning
confidence: 91%